The challenge of multidrug resistance in hospitalized pediatric patients with urinary tract infections - El Zein, Zeinab; Boutros, Celina F.; El Masri, Marwa; El Tawil, Elsy; Sraj, Maher; Salameh, Yara; Ghadban, Sarah; Salameh, Rim; El Baasiri, Silma; Haddara, Amani; Nasser, Mayse; Tabbara, Shady; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe choice of empirical treatment in pediatric urinary tract infections (UTIs) is increasingly complicated by the emergence of antibiotic resistance and the growing prevalence of multidrug-resistant organisms (MDROs). The aim of this study is to assess the resistance patterns of isolated uropathogens among children and adolescents hospitalized with UTIs in Lebanon; and determine the risk factors associated with MDRO-related UTIs over a 10-year period.MethodsA retrospective chart review was conducted at two tertiary medical centers in Beirut. Children and adolescents less than 18 years who were admitted, between January 1, 2011, and December 31, 2021, with the following ICD-10 codes: “urinary tract infection”, “cystitis” and/or “pyelonephritis “ were included. A case was excluded if the urine culture was polymicrobial or did not meet the definition of UTI we used. Univariate and multivariable logistic regression analyses were performed to identify risk factors for MDRO infections.ResultsAmong the 876 pediatric UTI cases included, 85% were above 2 months of age and 74.1% were females. 64.5% of 644 Escherichia coli and 61.9% of 114 Klebsiella spp. isolates met international MDR criteria. After a period of fluctuation, the proportion of MDROs began to steadily increase starting 2019 eventually surpassing the 2011 percentage by nearly 10% in 2021 (67.9%, p = 0.248). Only 2.1% of MDR E. coli and 2.9% of MDR Klebsiella spp. were resistant to carbapenems. However, aminoglycoside resistance was high ranging between 28.3% and 48.6%. Children aged ≥ 5 years were nearly twice as likely to present with an MDR uropathogen compared to those < 5 years of age (p < 0.001). Only a history of leukemia (p = 0.010, AOR = 4.248, 95% CI [1.412–12.778]) and antibiotic use in the preceding 30 days (p = 0.012, AOR = 2.045, 95% CI [1.167–3.582]) were found as independent risk factors for UTIs caused by MDROs in multivariable logistic regression.ConclusionThis study highlights the increasing threat of MDROs among pediatric UTIs. Recent antibiotic use was strongly associated with MDRO infections highlighting the urgent need for effective antimicrobial stewardship, re-evaluation of empiric treatment guidelines, and strict abidance by infection control measures.